Hepatoprotective effect of Chenopodium murale in mice - Mohammad Saleem; Bilal Ahmed; Muhammad Imran Qadir; . Mahrukh; Maria Rafiq; Mobasher Ahmad; Bashir Ahmad (Bangladesh Pharmacological Society, 2014)
Discovery of drugs has its roots in medicinal plants that appeal researchers to identify new therapeutical entities from plants. The current study was conducted to determine its hepatoprotective activity. The results showed that aqueous methanolic extract of Chenopodium murale (200 and 500 mg/kg) produced significant (p<0.001) decrease in paracetamol induced increased levels of liver enzymes (alanin transaminase, aspartate transaminase, alkaline phosphatase) and total bilirubin. These findings were further supported by histopathological investigations by microscope and detection of phytoconstituents having hepatoprotective potential e.g. qurecetin, kaempferol and gallic acid by HPLC. Conclusively aqueous methanolic extract of C. murale possess hepatoprotective activity against paracetamol induced liver damage in mice.